Invasibilidade de Hovenia dulcis Thunberg (Rhamnaceae) em Floresta Atlântica no sul do Brasil - Müller, Adelcio (Universidade Federal de São Carlos, 2015)
Biological invasions are a major threat to biodiversity conservation, and many studies have been conducted to give an answer to why some ecosystems are more invaded than others. Canopy openness and the litter thickness may be two of the factors to drive the seed germination and establishment of seedling of tree species. Hovenia dulcis is a tree widely distributed in southern Brazil, with intense natural regeneration. It has been reported to be dominant in many natural forests in the southern area of Brazil, where it is considered one of the main exotic species with occurrence in natural forest in this region. This research has the aim to assess whether the colonization time of the species on the remnants is relevant for the invasion process, and if the thickness of the litter and the openness of the canopy are important to forecast the abundance of the H. dulcis. We experimentally addressed which factors are related to the propagule pressure; if the propagule pressure is related to the seedling abundance, if the litter and the canopy openness are associated with the variation on the seedling recruitment; and whether survival and seedling recruitment vary between the treatments under and distant from the mother plant crown. To evaluate the importance of the residence time and the place variables upon the abundance variation of H. dulcis we assessed 25 subpopulations in ten forest remnants, totaling 250 subpopulations. For the trial study in eight remnants, four subpopulations (mother plants) were chosen in each of the eight, totaling 32 subpopulations. In each subpopulation, we delimitated a 1m² plot at the final plot of the mother plant crown, and another at the same direction at a distant twice the crown radius. In each remnant from two subpopulations it has been removed all litter from the plot and the others have just been marked. This experiment was followed for an eight-month period. It has been checked that the H. dulcis colonization time on the forest remnants was not important to forecast the abundance of seedlings and juveniles. Spatial variations on litter thickness and canopy openness explained most part of the H. dulcis abundance variation. This research has rejected the hypothesis that the propagule pressure is related to the H. dulcis seedlings abundance. It also showed that the canopy openness is not related with the abundance of the species. The germination has shown total independence from the extraction of the litter. Nonetheless, it has showed that the mother plant crown exert influence upon the survival of the seedlings, on treatments with or without litter. It has checked that the removal of litter increase significantly the recruitment of seedlings on environments without the influence of adults individuals of H. dulcis, thus showing that the disorders from different origins are fundamental for the initial colonization of the species. There are evidences that the presence of adults individuals of the species favor the establishment of its seedlings, regardless the presence of litter.
Keywords: Invasão biológica; Abertura do dossel; Serapilheira; Fragmentação florestal; Floresta Atlântica; Canopy openness; Litter layer; Forest fragmentation; Atlantic Forest,; Biological invasions; CIENCIAS BIOLOGICAS::ECOLOGIA